Label-Free Fluorescent Determination of Lead (II) Using DNAzyme and Thiazole Orange. (3rd July 2023) - Sun, Hongjing; Liu, Zheng; Li, Zhihong; Ma, Xinyue; Duan, Zixuan; Sun, Chunyan
Abstract: A simple and label-free fluorescent sensor based upon a specific DNAzyme (8–17 DNAzyme) and thiazole orange (TO) for monitoring Pb 2+ in water samples was described. The 8–17 DNAzyme was formed by an enzyme strand (17E) and a partially complementary substrate strand (17DS). Thiazole orange, the DNA intercalator, was nonfluorescent in aqueous solution while it intercalates into the 8–17 DNAzyme with a duplex structure resulting in strong fluorescence. In the presence of Pb 2+, the 17E was activated and cleaved the 17DS into two at the ribonucleoside adenosine (rA) position, leading to the disruption of the duplex structure. This Pb 2+ -induced conformational change led to the quenching of the fluorescence of thiazole orange, thus forming the basis for the label-free biosensor. Under the optimized conditions, the developed protocol exhibited sensitive determination of Pb 2+ with a detection limit of 0.73 nM and a linear range from 10 to 150 nM. The label-free fluorescent approach exhibited excellent selectivity, strong selectivity, and satisfactory analysis of a drinking water standard reference material and spiked river and tap water samples. Taking the advantage of the structure-switching 8–17 DNAzyme and the fluorescent intercalator of nucleic acids, this label-free sensor provides a new approach for routine screening of heavy metals based upon the DNAzyme.